Increased dosage of infliximab is a potential cause of Pneumocystis carinii pneumonia. Issue 1 (December 2016) - Iwama, Takuya; Sakatani, Aki; Fujiya, Mikihiro; Tanaka, Kazuyuki; Fujibayashi, Shugo; Nomura, Yoshiki; Ueno, Nobuhiro; Kashima, Shin; Gotoh, Takuma; Sasajima, Junpei; Moriichi, Kentaro; Ikuta, Katsuya
Abstract Methods Pneumocystis carinii pneumonia occasionally appears in immunodeficient patients. While several reports have shown thatPneumocystis carinii pneumonia occurred in the early phase of starting infliximab treatment in patients with Crohn's disease (CD), the present case suggests for the first time that an increased dosage of infliximab may also lead to pneumonia. Results A 51-year-old male had been taking 5 mg of infliximab for the treatment of CD for 10 years with no adverse events. Beginning in September 2013, the dose of infliximab had to be increased to 10 mg/kg because his status worsened. Thereafter, he complained of a fever and cough, and a CT scan revealed ground-glass opacities in the lower lobes of the bilateral lung with a crazy-paving pattern. Bronchoscopy detected swelling of the tracheal mucosa with obvious dilations of the vessels. A polymerase chain reaction using a bronchoalveolar lavage fluid sample detected specific sequences forPneumocystis jirovecii ; thus he was diagnosed withPneumocystis carinii (jirovecii) pneumonia. After discontinuing infliximab and starting antibiotic treatment, his symptoms and CT findings were dramatically improved. Conclusions The administration of an increased dosage of infliximab can causePneumocystis carinii pneumonia in CD patients.